2017
DOI: 10.1177/1534734617700539
|View full text |Cite
|
Sign up to set email alerts
|

Does Everything That’s Counted Count? Value of Inflammatory Markers for Following Therapy and Predicting Outcome in Diabetic Foot Infection

Abstract: To assess the severity of inflammation associated with diabetic foot infection (DFI), values of inflammatory markers such as white blood count (WBC), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and neutrophil to lymphocyte ratio (NLR) are often measured and tracked over time. It remains unclear if these markers can aid the clinician in the diagnosis and management of DFI, and ensure more rational use of antibiotics. Hospitalized adult patients (n = 379) with DFI were retrospectively assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
10
3
Order By: Relevance
“…Third, we conducted only the standard laboratory test for serum CRP. Thus, our findings may not apply to other inflammatory markers, such as pro‐calcitonin, 2,4,5 erythrocyte sedimentation rate, 2,4,6 interleukins 2, 6 or 8, 2,4 serum leukocyte counts, 4 tumour necrosis factors, 2,4 monocyte chemotactic protein, 4 macrophage inflammatory protein‐1 alpha, 4 neutrophil to lymphocyte ratios, 6 procollagen type 1 N propeptides, 2,4 or high‐resolution CRPs. However, these other markers are seldom used in daily clinical practice and all are more expensive than the standard CRP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Third, we conducted only the standard laboratory test for serum CRP. Thus, our findings may not apply to other inflammatory markers, such as pro‐calcitonin, 2,4,5 erythrocyte sedimentation rate, 2,4,6 interleukins 2, 6 or 8, 2,4 serum leukocyte counts, 4 tumour necrosis factors, 2,4 monocyte chemotactic protein, 4 macrophage inflammatory protein‐1 alpha, 4 neutrophil to lymphocyte ratios, 6 procollagen type 1 N propeptides, 2,4 or high‐resolution CRPs. However, these other markers are seldom used in daily clinical practice and all are more expensive than the standard CRP.…”
Section: Discussionmentioning
confidence: 86%
“…Evidence for the value of monitoring CRP in patients with DFIs remains unclear, especially as the CRP peak almost always lags behind the clinical evolution by ~2 days 1,5 . While some scientific literature supports using the quantitative serum CRP level in diagnosing the presence or severity of a DFI, 1,4–7 infectious diseases experts generally emphasize that no therapeutic decision should depend solely on this laboratory result 8,9 . We undertook this study to provide more information based on the utility of routine serum CRP controlling during DFI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…While their values could well assist in infection evaluation, reports on their efficacy widely vary in the DFU literature. While Michail et al reported significantly higher values in osteomyleitis cases compared to ulcers with soft tissue infection for both parameters,17 Ong et al found no significance 18. Furthermore…”
mentioning
confidence: 94%
“…Besides the MRI and the golden test of bone biopsy which both have high rates of sensitivity and specificity, the inflammatory markers such as CRP, ESR, procalcitonin and white cell count (WCC) have been extensively studied to differentiate between non‐infected and infected DFU 16 . However, few studies investigated the performance of WCC when differentiating between infected DFU with and without osteomyelitis 17–19 . Additionally, we are aware of only one study which recorded the variations of the platelet count for patients with IWGDF Grade 2 and 3 wounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation